Peningkatan Pendapatan Kelompok Tani Dengan Pemanfaatan Teknologi Hidroponik Berbasis IoT Pada Kelompok Tani Mekar Ayu Desa Sei Mencirim Deli Serdang - Noviandri, Dian; Hermawan, Indra; Indrawati, Asmah (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2024)
Community Service aims to increase the income of farmer groups by making hydroponics based IoT, the Mekar Ayu Farmers Group in Sei Mencirim Village has so far relied on horticultural farming by using agricultural land that is very dependent on nature and controlling hama by spraying anti-pests which results in the harvest being contaminated with these anti-pest substances. Farming groups have not utilized the empty land around the group members' housing which can be used to create various businesses that can increase their members' income, such as training in hydroponics, sowing water spinach and bok choi seeds. The problem is that there is no hydroponics yet, even though the land for laying hydroponics is mostly in the homes of members of farmer groups. So far, farmer groups have relied on agricultural land and knowledge of sowing seeds. IoT-based hydroponic production training solutions and seeding and pest control training until harvest arrives.